2003
DOI: 10.1088/0031-9155/48/15/302
|View full text |Cite
|
Sign up to set email alerts
|

Washout measurement of radioisotope implanted by radioactive beams in the rabbit

Abstract: Washout of 10C and 11C implanted by radioactive beams in brain and thigh muscle of rabbits was studied. The biological washout effect in a living body is important in the range verification system or three-dimensional volume imaging in heavy ion therapy. Positron emitter beams were implanted in the rabbit and the annihilation gamma-rays were measured by an in situ positron camera which consisted of a pair of scintillation cameras set on either side of the target. The ROI (region of interest) was set as a two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
129
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 19 publications
(19 reference statements)
5
129
1
Order By: Relevance
“…Positron emitter distributions were calculated by internally combining proton fluence with experimental cross sections (12). Besides the main (p, pn) channels on 12 C and 16 O yielding 11 C and 15 O (12), respectively, further proton interactions with N, O, Ca, and P, resulting in 11 C, 13 N, 38 K, and 30 P production, respectively, were included. Shorter-lived emitters were neglected because of the low-production cross-section and the offline PET imaging approach.…”
Section: Calculation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Positron emitter distributions were calculated by internally combining proton fluence with experimental cross sections (12). Besides the main (p, pn) channels on 12 C and 16 O yielding 11 C and 15 O (12), respectively, further proton interactions with N, O, Ca, and P, resulting in 11 C, 13 N, 38 K, and 30 P production, respectively, were included. Shorter-lived emitters were neglected because of the low-production cross-section and the offline PET imaging approach.…”
Section: Calculation Modelmentioning
confidence: 99%
“…This prohibits the application of compartment models, which are well-established in conventional tracer imaging. Previous animal studies on the washout of 10 C and 11 C implanted ions or 11 C resulting from autoactivation of 12 C beams indicated the existence of a fast (biologic half-life [T 1/2 , biof ] ≈(2-10 s), medium (T 1/2 , biom ≈100-200 s), and slow (T 1/2,bios ≈ 3,000-10,000 s) component of biologic decay in rabbit thigh muscle and brain (15,16). In our offline imaging approach, the fast and medium processes have already decayed at the time of imaging.…”
Section: Calculation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the biological washout effect in the metabolism of a living tissue is important for the verification of the absolute activity and the activity distribution of the positron-emitting nuclei induced by the proton irradiation. In studies in which the radioactive ion beam ( 11 C, 10 C) to a rabbit was irradiated, the decay curve has three components of a fast decay (decay constant *2-10 s), medium decay (decay constant *100-200 s), and slow decay (decay constant *3,000-10,000 s) [23,24]. The 50-65% of total activity is the fast and medium components.…”
Section: Measurement Of Activity With Pet-ct Apparatusmentioning
confidence: 99%
“…The simulation of using an on-line system showed losses in activity intensity from transportation to the offline system of up to 75%, depending on the type of tissue. Also, it was found that the effect of biological washout was lower than the previously estimated 50%-65%, although the overall effect was not quantified [37,38] . The study led by Parodi K took nine patients with different types of head and neck cancers and used a PET/…”
mentioning
confidence: 77%